Importance of shoulder girdle and finger flexor muscle endurance in advanced male climbers - Draga, Paweł; Rokowski, Robert; Sutor, Alexander; Pandurevic, Dominik; Michailov, Michail Lubomirov (Frontiers in Sports and Active Living, 2024)
Aim This study aimed to: (a) assess the relationships between climbing performance and finger and shoulder girdle muscle endurance; and (b) provide evidence on the validity of the specialized exercise tests used for the purpose. Materials and methods 28 male sport climbers (climbing ability 23 ± 2.43 IRCRA scale) performed four tests muscle failure, including two-finger hang tests (using 2.5 and 4 cm holds) and two variants of pull-up exercises (classical pull-ups and a combination of dynamic and isometric actions – the so-called Edlinger). Climbing performance and test results were subjected to correlation, taxonomic and regression analysis. Results The correlations between the results from all tests and climbing performance were notably strong (r between 0.54 and 0.61) and statistically significant (p<0.05). The taxonomic analysis indicated that the two variants of each test type reflect two different latent variables 2.5 cm and 4 cm finger hang durations were highly correlated (r=0.76,p<0.01). A similar correlation was found between the results from the pull-up tests (r=0.72,p<0.01). Thus, the finger hang and pull-up test results were determined to a high extent (43% and 49%, respectively) by factors that cannot be assessed when only one test of each type is used. The regression model of the two-finger tests allowed individual endurance profiles to be assessed. Conclusions The muscular endurance of the elbow flexors and shoulder girdle muscles predicts climbing performance within the specific sport level studied to a comparable degree as finger flexor endurance.The use of two variants of a test intended to assess one physical ability provided important details on a climber’s fitness.